APPLICATION OF GREEN BUILDING DESIGN PRINCIPLES IN THE DESIGN OF SMALL HOUSES - Dara Wisdianti (PT. Arsil Reka Engineering, 2025)
The increase in the population of Medan City has a direct impact on the increasing demand for housing and settlements, which is not always in line with environmental carrying capacity and the fulfillment of livable housing standards. Residential buildings contribute significantly to energy and water consumption, as well as environmental degradation, thus requiring a sustainable design approach. This study aims to formulate criteria and principles for the design of simple, livable houses by applying the concept of green buildings. The research method used is descriptive qualitative with a focus on the design of class 1a residential buildings. The study was conducted through a review of relevant regulations and standards, including the Ministry of Public Works and Public Housing's Green Building principles, the GREENSHIP Homes assessment system by the Green Building Council Indonesia, and livable housing indicators from the North Sumatra II Housing Provision Implementation Center. The results of the study show that the application of green building concepts in Small Houses can be realized through proper site management, optimization of natural lighting and ventilation, efficient use of energy and water, sustainable waste and wastewater management, and the selection of environmentally friendly building materials. The application of these principles can produce Small Houses that not only meet livable standards but also contribute to environmental sustainability.